2019
DOI: 10.1016/j.jagp.2019.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Declining Skeletal Muscle Mitochondrial Function Associated With Increased Risk of Depression in Later Life

Abstract: Objective: Late-life depression (LLD) is a chronic and heterogeneous disorder. Recent studies have implicated non-normative age-related processes in its pathogenesis. This investigation examined both cross-sectional and longitudinal associations between skeletal muscle mitochondrial function and LLD. Methods: Data from 603 men and women from the Baltimore Longitudinal Study on Aging were analyzed, of whom 167 provided data from a follow-up visit. Muscle bioenergetics was measured by postexercise recovery rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…A number of studies examined the links between the outcome of depression and physical health-related factors, such as bladder outlet obstruction, cerebral atrophy, cataract, stroke, epilepsy, body mass index and obesity, diabetes, urinary tract infection, forms of cancer, inflammatory bowel disorder, glaucoma, acne, urea accumulation, cerebral small vessel disease, traumatic brain injury, and disability in multiple sclerosis [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , ...…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies examined the links between the outcome of depression and physical health-related factors, such as bladder outlet obstruction, cerebral atrophy, cataract, stroke, epilepsy, body mass index and obesity, diabetes, urinary tract infection, forms of cancer, inflammatory bowel disorder, glaucoma, acne, urea accumulation, cerebral small vessel disease, traumatic brain injury, and disability in multiple sclerosis [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , ...…”
Section: Resultsmentioning
confidence: 99%
“…They are associated with cognitive impairment, physical comorbidity burden, and higher mortality risk. 10 , 11 , 12 , 13 , 14 , 15 Cellular senescence and changes in its cellular secretome (ie, the senescence-associated secretory phenotype or SASP) are other important hallmarks of biological aging. 16 The SASP factors comprise several signaling proteins associated with inflammatory control, tissue remodeling, cell growth, cell cycle control, and metabolic regulation.…”
Section: Introductionmentioning
confidence: 99%
“…. function in aging adults was also shown to be associated with clinically significant depressive symptoms (66). These lines of evidence support the critical regulatory roles of mitochondria in antidepressant functions.…”
Section: Targeting Mitochondria In Neurological Disease Treatmentmentioning
confidence: 75%
“…They observed that LRs displayed higher cytochrome c oxidase (COX) activity in the dentate gyrus, prefrontal cortex, and dorsal raphe compared to HRs ( 65 ). Apart from selected brain regions, a declining skeletal muscle mitochondrial function in aging adults was also shown to be associated with clinically significant depressive symptoms ( 66 ). These lines of evidence support the critical regulatory roles of mitochondria in antidepressant functions.…”
Section: Targeting Mitochondria In Neurological Disease Treatmentmentioning
confidence: 99%